β-Glucosidase BGLU42 is a MYB72-dependent key regulator of rhizobacteria-induced systemic resistance and modulates iron deficiency responses in Arabidopsis roots - Zamioudis, Christos (The New phytologist, 2014)
© 2014 The Authors. New Phytologist © 2014 New Phytologist Trust.